PEMBERDAYAAN UMKM MELALUI PELATIHAN DIGITAL MARKETING DAN EDUKASI GREEN PACKAGING DI POSBINDU DAHLIA INDAH RW 01, PESANGGRAHAN, JAKARTA SELATAN - Dezan Abdi Muhamad; Anindita Salsabila Ayutantri; Christy Yuniarti; Aisyah Indah Ramadhanti; Sugeng Priyanto; Dicky Arisudhana; Yugi Setyarko; Rizki Pratomo Sunarwibowo (Jurnal Padamu Negeri, 2025)
This Community Service Activity was carried out at the Integrated Development Post (POSBINDU) Dahlia Indah Rw 01 Pesanggrahan District, South Jakarta which aims to improve the knowledge and skills of Micro, Small, Medium Entreprise (MSME) actors in utilizing digital marketing and environmentally friendly product packaging. The method used is Application of Science and Technology to the Community in the form of training, which focuses on the use of e-commerce (Shopee), Promotion strategies through social media and content marketing and education that provides an understanding of green packaging product packaging. The results of this community service activity show an increase in the knowledge and skills of Micro, Small, Medium Entreprise (MSME) actors in managing digital marketing and product packaging. This activity is expected to provide a sustainable contribution in improving business and solving real problems.